2021
DOI: 10.1038/s41598-021-92315-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic history of human monkey pox infections in the Central African Republic between 2001 and 2018

Abstract: Monkeypox is an emerging infectious disease, which has a clinical presentation similar to smallpox. In the two past decades, Central Africa has seen an increase in the frequency of cases, with many monkeypox virus (MPXV) isolates detected in the Democratic Republic of Congo (DRC) and the Central African Republic (CAR). To date, no complete MPXV viral genome has been published from the human cases identified in the CAR. The objective of this study was to sequence the full genome of 10 MPXV isolates collected du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 48 publications
7
117
0
3
Order By: Relevance
“…However, despite the presence of these differences in the MPXV-M sequence compared with the MPXV-I sequence, phylogenetic analyses showed that the MPXV-M sequence is positioned in the CAR1 lineage of group II strains belonging to the Central African clade. The position of the MPXV-M sequence, along with the Bao (A4 and A5) and Bangassou (B2) sequences of 2016 and 2017, respectively, is identical to the phylogenetic analyses previously performed in a previous study using all CAR MPXV sequences obtained with Illumina sequencing 19 (Fig. 5 ).…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…However, despite the presence of these differences in the MPXV-M sequence compared with the MPXV-I sequence, phylogenetic analyses showed that the MPXV-M sequence is positioned in the CAR1 lineage of group II strains belonging to the Central African clade. The position of the MPXV-M sequence, along with the Bao (A4 and A5) and Bangassou (B2) sequences of 2016 and 2017, respectively, is identical to the phylogenetic analyses previously performed in a previous study using all CAR MPXV sequences obtained with Illumina sequencing 19 (Fig. 5 ).…”
Section: Resultssupporting
confidence: 61%
“…Although TGS is not the most suitable tool for rapid differential diagnosis of MPXV to distinguish it from Varicella-Zoster virus, its main advantage resides in the very fast identification of the origin of the strain. Our phylogenetic analysis showed that the MPXV-M sequence was sufficiently precise to position it correctly in the CAR1 lineage 19 . Molecular data obtained with TGS makes it possible to identify the relationships between detected cases more rapidly, especially those identified in the same city within a very short timeframe.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Amid the COVID-19 pandemic, the increasing reporting of cases of monkeypox virus infection in humans spreading through many countries outside Africa is a major reason for concern [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Monkeypox virus is a double-stranded DNA virus of the Poxviridae family which also includes the variola virus, the causative agent of smallpox [ 14 , 15 ].…”
mentioning
confidence: 99%